Tenosynovitis Evaluation Using Image Fusion and B-Flow – A Pilot Study on New Imaging Techniques in Rheumatoid Arthritis Patients - Ammitzbøll-Danielsen, Mads; Glinatsi, Daniel; Torp-Pedersen, Søren; Møller, Jacob M.; Naredo, Esperanza; Ostergaard, Mikkel; Terslev, Lene (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Aim The aim of this study was to compare the assessment of tenosynovitis by ultrasound (US) and magnetic resonance imaging (MRI) using the image fusion technique and to investigate whether US B-flow imaging (BFI) is an alternative to Doppler US when assessing tenosynovitis.Materials and Methods 15 patients with rheumatoid arthritis (RA) had US-verified tenosynovitis in the wrist/hand. An MRI was performed of the wrist/hand with subsequent repeated US and image fusion. Images were compared in three steps: 1. Visual image comparison, 2. Quantitative measurement of transverse areas of the affected tendon and tendon sheath, using two tendon measures on MRI, area 1 and area 2, excluding and including partial volume artifacts, respectively, 3. Assessment using the OMERACT semi-quantitative scoring systems for US and MRI. Furthermore, BFI was assessed as: 0: No flow, 1: Focal flow, 2: Multifocal flow, 3: Diffuse flow, in the tendon sheath.Results The median areas on US and MRI (areas 1 and 2) were 0.16 cm2 (25;75 pctl: 0.10; 0.25), 0.9 cm2 (0.06; 0.18) and 0.13 cm2 (0.10; 0.25), respectively, for included tendons and 0.18 cm2 (0.13; 0.26), 0.27 cm2 (0.20; 0.45) and 0.23 cm2 (0.16; 0.40) for tendon sheaths. No statistically significant difference was found between US tendon area and MRI tendon area 2 (Wilcoxon’s test; p = 0.47). Overall, the agreement between grayscale and color Doppler (CD) US and MRI tenosynovitis visualization and scoring was good, but not between CD and BFI.Conclusion US and MRI have high agreement using image fusion for the assessment of tenosynovitis when partial volume artifacts are taken into account. BFI is not an alternative to CD for the measurement of slow flow in tenosynovitis.
Keywords: tendons; ultrasound; arthritides; MR imaging; ultrasound Doppler